2007
DOI: 10.1029/2007jd008459
|View full text |Cite
|
Sign up to set email alerts
|

Global budget of CO, 1988–1997: Source estimates and validation with a global model

Abstract: [1] We present a model study of carbon monoxide for 1988-1997 using the GEOS-Chem 3-D model driven by assimilated meteorological data, with time-varying emissions from biomass burning and from fossil fuel and industry, overhead ozone columns, and methane. The hydroxyl radical is calculated interactively using a chemical parameterization to capture chemical feedbacks. We document the inventory for fossil fuels/industry and discuss major uncertainties and the causes of differences with other inventories that giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
486
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(506 citation statements)
references
References 140 publications
(299 reference statements)
16
486
2
2
Order By: Relevance
“…It can serve as an abundant source of HO X , particularly in the free and upper troposphere [Tie et al, 2003]. It is also an important source of important atmospheric constituents such as formaldehyde [e.g., Riemer et al, 1998] and carbon monoxide [e.g., Duncan et al, 2007]. These engender a critical effect on the oxidative capacity of the atmosphere and the radiative budget.…”
Section: Introductionmentioning
confidence: 99%
“…It can serve as an abundant source of HO X , particularly in the free and upper troposphere [Tie et al, 2003]. It is also an important source of important atmospheric constituents such as formaldehyde [e.g., Riemer et al, 1998] and carbon monoxide [e.g., Duncan et al, 2007]. These engender a critical effect on the oxidative capacity of the atmosphere and the radiative budget.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol is primarily released to air from terrestrial plants (during growth and decay); other identified sources include industrial emissions, biomass and biofuel burning, and atmospheric production (1)(2)(3)(4)(5). Methanol reacts with OH in the troposphere with a photochemical lifetime of ∼10 d, leading to formaldehyde (6) and carbon monoxide (7), among other products. Observations suggest that methanol can be further removed from air via deposition to land (8) and to the sea surface (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Since it is an important precursor of carbon monoxide, formaldehyde and tropospheric ozone, it plays an important role in the global tropospheric chemistry (Tie et al, 2003;Millet et al, 2006;Duncan et al, 2007;Choi et al, 2010;Hu et al, 2011). Field and laboratory measurements have been carried out to characterize methanol sources and sinks.…”
Section: Introductionmentioning
confidence: 99%